1991
DOI: 10.1139/x91-157
|View full text |Cite
|
Sign up to set email alerts
|

Simple, flexible, trigonometric taper equations

Abstract: There have been numerous approaches to modeling stem form in recent decades. The majority have concentrated on the simpler coniferous bole form and have become increasingly complex mathematical expressions. Use of trigonometric equations provides a simple expression of taper that is flexible enough to fit both coniferous and hardwood bole forms. As an illustration, we applied trigonometric taper equations to examples from thinned and unthinned slash pine (PinuselliottiiEngelm. var. elliottii), willow oak (Quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 4 publications
0
40
0
7
Order By: Relevance
“…A large number of compatible taper-volume systems based on type (1) have been created for oak species in Greece, America, Denmark, Spain and Mexico (Hilt 1980, Thomas & Parresol 1991, Tarp-Johansen et al 1997, Pompa-García et al 2009, Kitikidou 2010. Simple equations (Hilt 1980, Thomas & Parresol 1991, Kitikidou 2010, variable exponent equations (Tarp-Johansen et al 1997) or segmented-polynomial equations (Pompa-García et al 2009) were chosen for taper modelling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of compatible taper-volume systems based on type (1) have been created for oak species in Greece, America, Denmark, Spain and Mexico (Hilt 1980, Thomas & Parresol 1991, Tarp-Johansen et al 1997, Pompa-García et al 2009, Kitikidou 2010. Simple equations (Hilt 1980, Thomas & Parresol 1991, Kitikidou 2010, variable exponent equations (Tarp-Johansen et al 1997) or segmented-polynomial equations (Pompa-García et al 2009) were chosen for taper modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Simple equations (Hilt 1980, Thomas & Parresol 1991, Kitikidou 2010, variable exponent equations (Tarp-Johansen et al 1997) or segmented-polynomial equations (Pompa-García et al 2009) were chosen for taper modelling. There has been no similar research for Quercus variabilis Blume, an important broadleaf tree species in North China, prior to the study reported here.…”
Section: Introductionmentioning
confidence: 99%
“…La literatura actual incluye modelos de ahusamiento lineales (Allen, 1991;Bruce et al, 1968;Kozak, Munro, & Smith, 1969;Lowell, 1986;Real & Moore, 1986;Renteria & Ramirez, 1998), no lineales (Demaerschalk, 1972(Demaerschalk, , 1973Sharma & Oderwald, 2001;Sharma & Zhang, 2004), segmentados (Cao, Burkhart, & Max, 1980;Max & Burkhart, 1976;Parresol, Hotvedt, & Cao, 1987;Valenti & Cao, 1986) y trigonométricos (Thomas & Parresol, 1991). Esa gama incluye desde modelos diferenciables e integrables, hasta modelos que requieren de la integración numérica para la obtención del volumen del fuste.…”
Section: Introductionunclassified
“…Kozak et al, 1969), logarithmic (Demaerschalk, 1972), trigonometric (Thomas & Parresol, 1991), and other forms (e.g. Biging, 1984) have been developed for trees from a wide range of species and geographical areas.…”
Section: Introductionmentioning
confidence: 99%